Determination of the influence of the geometric parameters of rope blocks on the durability of the rope - Fidrovska, Nataliia Mykolaiivna; Karavan, Ruslan Andriyovich; Ptushka, Anastasiia Serhiivna; Yazlovytska, Olena Volodymyrivna; Фідровська, Наталя Миколаївна; Караван, Руслан Андрійович; Птушка, Анастасія Сергіївна; Язловицька, Олена Володимирівна (Харківський національний автомобільно-дорожній університет, 2023)
Problem. The durability of crane ropes is very important, as it ensures not only the main costs of operating the lifting machine, but also the safety of loading and unloading operations The operating conditions of the rope have a very significant effect on the period of its use, but they are not always taken into account. Yes, the method of calculating the rope, which is reflected in the standard, does not take into account the operating conditions of the rope, so it is very difficult to accurately predict its durability. In modern educational and reference literature, the influence of the size and geometry of rope blocks on the durability of lifting ropes is underestimated. The main criterion that is taken into account when choosing a rope according to existing methods is the tensile strength of the rope, although as shown by the research of many famous scientists, the wires of the rope break precisely as a result of bending on the blocks and the drum. The diameter of the block is selected depending on the diameter of the rope and the mode of operation of the lifting mechanism. The material of the block and its geometry are not taken into account at all when choosing the type of rope and its diameter, while the wear of the surfaces of the rope and the block greatly affects the durability of these elements of the lifting mechanism. Determining the factors that affect the wear of the rope and the reduction of its durability is quite an important task and requires not only theoretical, but also experimental research. At the same time, ropes of different designs and diameters were considered. At the same time, ropes of different designs and diameters were considered. This made it possible to evaluate the influence of various elements of the rope and the block on the predicted durability of the rope. The conducted research made it possible to improve the formula of B. Kovalsky, which he proposed for choosing the diameter of the rope according to the service life. The dependence of the influence of the opening angle of the block groove, which is determined from the condition of the reduction of rope torsion during its deviation, on the durability of the rope was obtained. In order to obtain a more realistic picture of the load of the rope that bends on the block and drum, the calculation scheme was improved and the number of factors that have a significant impact on the durability of the rope was increased. The results of the research significantly bring the rope load conditions during bending on the block and drum closer to real values.
Визначення впливу геометричних параметрів канатних блоків на довговічність канату
Keywords: rope; lifting mechanism; rope block; rope durability; rope deflection angle; канат; механізм підйому; канатний блок; довговічність канату; кут відхилення канату; 621.874; 10.30977/BUL.2219-5548.2023.101.2.137